Questioning the historicity of Jesus : why a philosophical analysis elucidates the historical discourse - Lataster, Raphael, (Value Inquiry Book Series;, 2019)
This volume moves beyond the mainstream scholarly scepticism over the Christ of Faith and considers if there is sufficient evidence to establish the existence of the more mundane Historical Jesus. Using the logical tools of the analytic philosopher, Lataster finds that the relevant sources are unreliable as historical documents, and that the key method of those purporting that the Historical Jesus existed is to appeal to sources that do not exist. Considering an ancient hypothesis suggesting that Jesus began as a celestial messiah that certain Second Temple Jews already believed in, and was later allegorised in the Gospels, Lataster discovers that it is more reasonable to at least be agnostic over Jesus' historicity.